2021
DOI: 10.3390/ijms22126630
|View full text |Cite
|
Sign up to set email alerts
|

Epitranscriptomics of Ischemic Heart Disease—The IHD-EPITRAN Study Design and Objectives

Abstract: Epitranscriptomic modifications in RNA can dramatically alter the way our genetic code is deciphered. Cells utilize these modifications not only to maintain physiological processes, but also to respond to extracellular cues and various stressors. Most often, adenosine residues in RNA are targeted, and result in modifications including methylation and deamination. Such modified residues as N-6-methyl-adenosine (m6A) and inosine, respectively, have been associated with cardiovascular diseases, and contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 175 publications
(281 reference statements)
0
8
0
Order By: Relevance
“…This new field of study extends further understanding of epigenetics from the perspective of RNA, where the terminologies are adopted from epigenetics, including writers, readers, and erasers to categorize epitranscriptomic enzymes. These enzymes are active in many tissues and cell types, whose dyregulations are linked to a variety of disorders and critical diseases, such as cardiovascular disease ( 9 , 10 ). These epitranscriptomic enzymes mark all kinds of RNA species, including mRNAs and ncRNAs, such as ribosomal RNAs (rRNAs), transfer RNAs (tRNAs), miRNAs, and lncRNAs ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…This new field of study extends further understanding of epigenetics from the perspective of RNA, where the terminologies are adopted from epigenetics, including writers, readers, and erasers to categorize epitranscriptomic enzymes. These enzymes are active in many tissues and cell types, whose dyregulations are linked to a variety of disorders and critical diseases, such as cardiovascular disease ( 9 , 10 ). These epitranscriptomic enzymes mark all kinds of RNA species, including mRNAs and ncRNAs, such as ribosomal RNAs (rRNAs), transfer RNAs (tRNAs), miRNAs, and lncRNAs ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prospective controlled observational cohort studies, such as the The Ischemic Heart Disease Epitranscriptomics and Biomarkers (IHD-EPITRAN) study ( www.ihd-epitran.com ), help us to shed light into this fascinating development. 412 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have also shown the m 6 A-methylation landscape of human CAD and aortic dissection. 62,63 A 2019 study showed that C57BL/6J mice subjected to transient middle cerebral artery occlusion displayed increased total m 6 A levels after 12 and 24 hours of reperfusion compared with sham operated animals. 64 The authors of this study demonstrated the presence of differentially hyper- and hypo-methylated mRNAs and long noncoding RNAs belonging to biological processes associated with inflammation, apoptosis, and transcriptional regulation after stroke.…”
Section: Covalent Reversible Rna Modificationsmentioning
confidence: 99%